TINJAUAN YURIDIS TERHADAP PEMBATALAN SITA EKSEKUSI OLEH BADAN PENYELESAIAN SENGKETA KONSUMEN DITINJAU DARI UNDANG-UNDANG NO 42 TAHUN 1999 TENTANG JAMINAN FIDUSIA - Hutagaol, Duma Novianty; Fauziah, Anisa (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Since the end of 2013, the Supreme Court has ruled that disputes arising from the implementation of consumer financing agreements, whether based on fiduciary agreements or collateral rights, are not considered consumer disputes. Therefore, the BPSK does not have the authority to adjudicate them. The issue addressed in this thesis is the legal validity of the cancellation of the execution of fiduciary collateral by the BPSK, as reviewed under Law No. 42 of 1999 in the Supreme Court decision No. 234/Pdt.Sus/Bpsk/2022/Pn,Pdg. How does the judge consider the fiduciary collateral executed by the creditor in the Supreme Court decision 234/Pdt.Sus/Bpsk/2022/Pn,Pdg? The research method used is normative legal research using data from various literature sources, such as books, journals, regulations, etc. Data analysis was conducted using a normative approach. The research method employed was normative legal research utilizing literature data from various books, journals, regulations, and other sources. Data analysis was conducted using a normative approach. The research findings indicate that the cancellation of the execution seizure by the BPSK contradicts the provisions of Law No. 42 of 1999 on Fiduciary Guarantees, where the creditor has preferential rights over the fiduciary object. The Supreme Court overturned the BPSK's decision, which had previously seized the collateral object, and the creditor's execution was contrary to Constitutional Court Decision No. 18/PUU-XVII/2019